The Antibacterial Drug Candidate SBC3 is a Potent Inhibitor of Bacterial Thioredoxin Reductase. (17th December 2020) - O'Loughlin, Jennie; Napolitano, Silvia; Alkhathami, Fahad; O'Beirne, Cillian; Marhöfer, Daniel; O'Shaughnessy, Megan; Howe, Orla; Tacke, Matthias; Rubini, Marina
Abstract: Antibiotic resistance is a growing problem for public health and associated with increasing economic costs and mortality rates. Silver and silver‐related compounds have been used for centuries due to their antimicrobial properties. In this work, we show that 1, 3‐dibenzyl‐4, 5‐diphenyl‐imidazol‐2‐ylidene silver(I) acetate/NHC*‐Ag‐OAc (SBC3) is a reversible, high affinity inhibitor of E. coli thioredoxin reductase (TrxR; K i =10.8±1.2 nM). Minimal inhibition concentration (MIC) tests with different E. coli and P. aeruginosa strains demonstrated that SBC3 can efficiently inhibit bacterial cell growth, especially in combination with established antibiotics like gentamicin. Our results show that SBC3 is a promising antibiotic drug candidate targeting bacterial TrxR. Abstract : Silver lining : Antibiotic resistance jeopardizes the effective treatment of infectious diseases and represents an increasing threat to public health. We discovered that the N ‐heterocyclic carbene 1, 3‐dibenzyl‐4, 5‐diphenylimidazol‐2‐ylidene silver(I) acetate (SBC3) is a potent inhibitor of bacterial thioredoxin reductase that proved to be highly effective against resistant Gram‐negative nosocomial isolates.